Long-Term Housing and Intimate Partner Violence: Journeys to Healing. Issue 4 (November 2018) - Hetling, Andrea; Dunford, Amy; Lin, Sarah; Michaelis, Emily
For survivors of intimate partner violence (IPV), safe, affordable, long-term housing is a critical aspect of establishing a life free from abuse. New permanent housing models for IPV survivors, which are emerging across the United States, are designed to meet the basic need of shelter and must at the same time be focused on meeting the needs of survivors of IPV. Using an in-depth qualitative case study of a new supportive housing program serving 10 IPV survivors and their children, our research project examines how housing helps residents heal from trauma. We use constructivist grounded theory and a feminist perspective to give voice to the women and construct an in-depth understanding of their perspectives. Data collection spanned 7 months and included two rounds of individual interviews and four focus groups. Data analysis utilized open-ended coding and constant comparison to inform theories on trauma and trauma-informed care. Our findings indicate that safe, affordable housing is related to the ability of IPV survivors to recover from past trauma. Based on our findings, theories and practice frameworks should consider housing stability as an integral component in the healing process. We also discuss policy and practice implications to incorporate trauma-informed practices in housing models.